Penerapan Inovasi Produk Teh pada PT Sila Agri Inovasi - Adil Fadillah; Raden Wina Ramadina; Danti Astrini; Soei Khim; Diah Kusumayanti (Jurnal Aplikasi Bisnis Kesatuan, 2026)
Indonesian consumers may be more familiar with specialty coffee. Similar to the marketing of coffee, the global tea industry also promotes specialty tea as a premium product. Specialty tea refers to tea produced through specific cultivation, harvesting, and processing methods to create distinctive characteristics. Currently, many people in the wider community do not consume herbal products due to limited awareness, particularly regarding their effectiveness, unreliable preparation methods, and the commonly perceived unpleasant aromas and flavors, such as blandness or sourness. In addition, preparation techniques and formulations are often considered less than ideal. This study aims to identify: (1) the implementation of product innovation at PT Sila Agri Inovasi; (2) the obstacles encountered in implementing product innovation at PT Sila Agri Inovasi; and (3) the strategies used to overcome these obstacles. The findings indicate that: (1) PT Sila Agri Inovasi has implemented product innovation by developing a product called Sila Tea. Sila Tea is a blend of pure tea, fruits, flowers, and spices that produces distinctive colors, flavors, and aromas. The addition of citrus fruit also gives the tea a naturally sweet taste; (2) the primary obstacle is the limited public knowledge of artisan tea in Indonesia. Indonesian consumers are generally more familiar with pure teas, such as green tea, black tea, and red tea. Consequently, many consumers remain unaware of the various health benefits offered by artisan tea; and (3) to overcome this obstacle, the company can educate the public about Indonesian tea products and emphasize that Indonesian tea has excellent quality, particularly when blended with fruits and spices. Sila Tea offers innovative products with potential health benefits. Although the combination of tea and spices may be unfamiliar to Indonesian consumers, Sila Tea incorporates citrus fruits and flowers to produce a lighter flavor and natural sweetness.   Keywords: innovation, tea, marketing, product.